A vineyard morning - Stone, Jean, 1948- (Stone, Jean, 1948- Vineyard novel, 2021)
Life is usually quiet during the off-season on Martha's Vineyard, but not for island newbie and bestselling novelist Annie Sutton...Finallly settled into her adopted island home, Annie is looking forward to writing her next mystery, making soap for her new business, and starting renovations on the Inn she plans to open by the summer. She's also enjoying spending more time with local police sergeant John Lyons, the man she's only just gotten comfortable calling her boyfriend. She's even starting to relish her relationship with John's teenage daughter, Lucy. It's probably not the best moment for a visit from the biological mother Annie only recently met. Still, it's high time she got to know the mysterious Donna MacNeish... But Donna's visit isn't merely a social call---she's come to share some devastating news. Seeking solace in an outing with Lucy, Annie and the teen stumble upon skeletal remains on the Inn's property, a finding that calls a halt to all construction while the police investigate. Desperate for answers, Annie starts asking questions of her own. But when secrets about her own past bring shattering revelations, suddenly everything Annie understands about love and loyalty is tested--and she wonders if the ties that bind her to her beloved community will reach a breaking point...